2022
DOI: 10.1088/1402-4896/aca56b
|View full text |Cite
|
Sign up to set email alerts
|

Structure, half-metallic and magnetic properties of bulk and (001) surface of Rb2XMoO6 (X = Cr, Sc) double perovskites: a DFT + U study

Abstract: Half-metallic (HM) ferromagnets (HM-FMs) with large HM gap and high Curie temperature (TC) have a great importance in the field of spintronics. In this study, the geometric features, electronic structure and magnetism of two new double perovskites (DPs) represented by Rb2XMoO6 (X=Cr, Sc) were explored in bulk phase and (001) surface using quantum mechanical total energy calculations based on density functional theory (DFT). The results showed that Rb2CrMoO6 (RCMO) and Rb2ScMoO6 (RSMO) has an optimized lattice … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…Cohesive and formation energies are useful chemical properties for analyzing the strength of atomic forces that hold solids together and revealing the phase stability of any material. 66–70 The formation energy of a material is calculated by subtracting the sum of energies of the individual constituent atoms from the equilibrium energy of the primitive cell of that material divided by the total number of atoms in the primitive cell as described in eqn (18).Here, E b x ( x = Ba, Na, O, Cl, Br, I) are the bulk elemental energies calculated as per atom from the stable bulk phase of each element; 71 e.g. , we have used cubic Ba, cubic Na, trigonal O, orthorhombic Cl, cubic Br, and cubic I bulk structures, which have 4, 1, 6, 8, 3, and 2 atoms per cell, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Cohesive and formation energies are useful chemical properties for analyzing the strength of atomic forces that hold solids together and revealing the phase stability of any material. 66–70 The formation energy of a material is calculated by subtracting the sum of energies of the individual constituent atoms from the equilibrium energy of the primitive cell of that material divided by the total number of atoms in the primitive cell as described in eqn (18).Here, E b x ( x = Ba, Na, O, Cl, Br, I) are the bulk elemental energies calculated as per atom from the stable bulk phase of each element; 71 e.g. , we have used cubic Ba, cubic Na, trigonal O, orthorhombic Cl, cubic Br, and cubic I bulk structures, which have 4, 1, 6, 8, 3, and 2 atoms per cell, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Mebed et al calculated the cohesive and formation energies for Rb 2 CrMoO 6 as +4.531 and −1.887 in eV per atom, and for the Rb 2 ScMoO 6 DP structure as +5.065, and −1.826 in eV per atom, respectively. 71 Mir et al reported the cohesive energies of Ca 2 MgWO 6 and Sr 2 MgWO 6 DP oxides as 6.18 and 5.74 eV per atom, respectively. 75 Manzoor et al calculated the formation energies for the Sr 2 SbTaO 6 DP structure as −2.886 eV per atom and for Sr 2 BiTaO 6 DP oxide as −2.798 eV per atom.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Unique fluoro-perovskites keep showing a wide range of remarkable properties, such as ongoing advanced technology applications and the ability to incorporate almost all elements of the periodic table K 2 CuBiCl 6 [ 19 ], Rb 2 CrMoO 6 [ 20 ], and Rb 2 GeSnI 6 [ 21 ], which makes their study fascinating. Highly mobile fluoro-perovskite RBeF 3 (R K and Li) layers are of particular interest as they reflect solar UV radiation and provide new layer components and broad bandgap substances for light reflection.…”
Section: Introductionmentioning
confidence: 99%